Increased village potential towards creative and independent communities - Sihombing, Yuan Alfinsyah; Hulu, Ester Rinaldi; Hutabarat, Tini Ayuna; Puspitasar (Talenta Publisher, 2019)
Community service activities are divided into three stages, namely preparation, implementation of activities on site, and evaluation. These community service activities have been carried out in Pematang Marihat Village, Siantar Marimbun District, Pematangsiantar City in the form of health check-up activities namely blood sugar and blood pressure checks, health education, healthy exercise, PHBS which is specialized in dental and mouth hygiene, hands and nails, reactivation hydroponics, planting vegetable seeds in polybags, making Family Medicinal Plants (TOGA), making compost from straw, learning groups and teaching activities in schools. The implementation of these activities is expected to benefit the local community. Get closer to the relationship of higher education with the community where KKN students are located. Train students in studying social phenomena that occur in the community. Providing space and land for students to express their application of theories that have been obtained on campus to become agents of change in society. The activities carried out in support of these activities are morning activities, healthy exercise, non-communicable disease counseling, health and clean lifestyle counseling, blood sugar and blood pressure checks, reactivation of hydroponics, Family Medicinal Plant Manufacturing (TOGA), compost fertilizer production from straw. With the completion of the work program of KKN (Real Work Lecture) Group 2 Pematang Marihat Village, Siantar Marimbun District, Pematangsiantar City, the translation of the Tri Dharma of Higher Education to the community can be carried out well. Through the implementation of this Community Service Program, we can apply the knowledge gained in college in the form of community service in Pematang Marihat Village.